(untitled) (Revista de Ciências Agroveterinárias, 2024)
Integrating information on drought incidents into planning and analysis processes can assist land, water, and urban managers to prepare more effectively for water-related hazards. This study aims to assess the spatiotemporal characteristics of drought upstream of the Little Zab River Basin from 2004 to 2018 by integrating satellite-derived data and meteorological indices to address the limitations of gauge measurements. The Coefficient of Variation (CV) was used to analyze precipitation inconsistency on an annual timescale. The Reconnaissance Drought Index (RDI), the second Modified Soil-Adjusted Vegetation Index (MSAVI2), and the Normalized Difference Water Index (NDWI) were adopted as meteorological, agricultural, and hydrological drought indices, respectively. Additionally, the Pearson Correlation Coefficient (PCC) was applied to comprehend the relationship between the implemented variables. Findings exhibited moderate (22.4%–28.5%) CV values in the annual precipitation data. RDIst results identified a significant extreme-to-severe drought event during the hydrological year 2007–2008, persisting with lower intensities into 2008–2009 across most observatories. The NDWI values displayed that the surface area of Dukan Reservoir reached its minimum extents of 133 km2 and 123 km2 in 2008 and 2009, respectively. Although mean MSAVI2 values competently detected the 2008 and 2009 drought incidents, those precipitation deficiencies later harmed the vegetation cover in 2010. There was a significant positive correlation between precipitation, RDIst, NDWI, and mean MSAVI2 values. the study concludes that meteorological drought in the research region instantly leads to hydrological drought, resulting in agricultural drought with a one-year lag.